1995
DOI: 10.1177/002204269502500110
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Intoxication and Impairment at Arrest among Adults Convicted of Driving under the Influence of Alcohol

Abstract: Making the decision to drive after drinking potentially involves assessing personal levels of intoxication and impairment. This paper reports driving under the influence (DUI) convictees' recalled perceptions of their intoxication, impairment, and reported blood alcohol concentration (BAC) on the day or night of their arrest. Respondents' recalled levels of intoxication and impairment corresponded to their reported BAC across self-labeled categories of drinking patterns. No significant differences in these per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Individuals indicated that as they felt more impaired, they would be less likely to drive, felt the likelihood of another intervening in preventing them from drinking and driving to be greater, and would be more receptive to an intervention effort by another. Previous research has suggested that individuals may choose to drink and drive, despite feeling impaired (Lewis & Merz, 1995). Indeed, in the current study, perceived likelihood of an accident or arrest were found to play a role in one's decision of whether or not to drink and drive, over and above perceived level of impairment.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…Individuals indicated that as they felt more impaired, they would be less likely to drive, felt the likelihood of another intervening in preventing them from drinking and driving to be greater, and would be more receptive to an intervention effort by another. Previous research has suggested that individuals may choose to drink and drive, despite feeling impaired (Lewis & Merz, 1995). Indeed, in the current study, perceived likelihood of an accident or arrest were found to play a role in one's decision of whether or not to drink and drive, over and above perceived level of impairment.…”
Section: Discussionmentioning
confidence: 44%
“…Despite these harmful consequences, many individuals continue to drink and drive, revealing the need for an enhanced understanding of variables influencing one's decision to drink and drive. drink and drive (Lewis & Merz, 1995;Turrisi & Jaccard, 1991). Lewis and Merz (1995) found that although individuals considered their level of impairment, close to half of participants (48%) drove even though they were aware that they should be careful driving due to the amount of alcohol they had consumed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were tested in small groups and were isolated from one another and monitored, as in our previous field studies. Computerized assessments have been used successfully in problematic populations in previous research .…”
Section: Methodsmentioning
confidence: 99%
“…bars and liquor stores [UK equivalents being pubs, off-licences and supermarkets]) have become more accepted within society, with some estimates finding that as much as half of all Americans will attend a bar at least once within any given year (Okraku, 1998;Green & Plant, 2007). As such, the very act of drinking at these establishments and then driving oneself home is believed by some to have become a part of our culture (Lewis et al, 1995). Another factor in this argument is the belief that those who drink and drive have only an estimated 1 in 100 chance of getting caught during the act (Labrie et al, 2007), meaning that offenders may believe they have little or no chance of being caught when driving home from these establishments.…”
Section: Introductionmentioning
confidence: 99%